The relationship between group cohesion, group norms, and perceived social loafing in soccer teams - Hoigaard, Rune; Safvenbom, Reidar; Tonnessen, Finn Egil (2006)
The purpose of this study was to examine the relationship between group cohesion, group norms, and perceived social loafing among 118 soccer players playing junior league in Norway. Each player completed a questionnaire assessing group cohesion (task cohesion and social cohesion), team norms (productive norms, role involvement, and social support norms), and perceived social loafing. As predicted, all cohesion- and team-norm sub-scales were negatively correlated with perceived social loafing. Furthermore, the results showed that the players? attraction to their team?s task as well as their perception of the productive- and social-support norm predicted perceptions of social loafing. A significant three-way interaction between task cohesion, social cohesion, and performance norm emerged. The analysis showed that the combination of high social cohesion, low task cohesion, and low team norms seems to underlie perceptions of social loafing.